How much is enough? Assessing the influence of neighborhood walkability on undertaking 10-minute walks - Boisjoly, Geneviève; Wasfi, Rania; El-Geneidy, Ahmed (Journal of Transport and Land Use, 2018)
Neighborhood walkability is increasingly perceived as an effective way to support individuals’ health, since living in a walkable environment is associated with increases in utilitarian walking. Yet, while people are more likely to walk in more walkable neighborhoods, increased walkability can also lead to walking shorter distances, thus mitigating the positive health outcomes associated with walkable environments. Given that the World Health Organization recommends physical activity to be performed in sessions of at least 10 minutes, the aim of this research is to explore the relationship between neighborhood walkability and individuals’ likeliness of walking in sessions of at least 10 minutes. A multilevel logistic regression is generated using data from the Montreal, Canada, 2013 Origin-Destination Survey. The results show that the probability of walking at least 10 minutes for shopping purposes is equally high in the 80-89 and 90-100 Walk Score neighborhoods. In contrast, car ownership is a strong predictor of walking at least 10 minutes, especially in higher Walk Score neighborhoods. These findings suggest that transport policies aimed at reducing car ownership, combined with land use policies, can be most effective in supporting the minimal 10-minute sessions of walking for shopping purposes. This study provides a nuanced assessment of walkability and is of relevance to researchers and planners wishing to assess and develop policies for increasing health benefits through active transportation.